Dosimetric benefit of adaptive magnetic resonance-guided stereotactic body radiotherapy of liver metastases - Weykamp, Fabian; Katsigiannopulos, Efthimios; Piskorski, Lars; Regnery, Sebastian; Hoegen-Saßmannshausen, Philipp; Ristau, Jonas; Renkamp, Claudia Katharina; Liermann, Jakob; Forster, Tobias; Uzun-Lang, Kristin; König, Laila; Rippke, Carolin; et al. (Cancers, 2022)
(1) Background: To assess dosimetry benefits of stereotactic magnetic resonance (MR)-guided online adaptive radiotherapy (SMART) of liver metastases. (2) Methods: This is a subgroup analysis of an ongoing prospective registry including patients with liver metastases. Patients were treated at the MRIdian Linac between February 2020 and April 2022. The baseline plan was recalculated based on the updated anatomy of the day to generate the predicted plan. This predicted plan could then be re-optimized to create an adapted plan. (3) Results: Twenty-three patients received 30 SMART treatment series of in total 36 liver metastases. Most common primary tumors were colorectal- and pancreatic carcinoma (26.1% respectively). Most frequent fractionation scheme (46.6%) was 50 Gy in five fractions. The adapted plan was significantly superior compared to the predicted plan in regard to planning-target-volume (PTV) coverage, PTV overdosing, and organs-at-risk (OAR) dose constraints violations (91.5 vs. 38.0%, 6 vs. 19% and 0.6 vs. 10.0%; each p < 0.001). Plan adaptation significantly increased median BEDD95 by 3.2 Gy (p < 0.001). Mean total duration of SMART was 72.4 min. (4) Conclusions: SMART offers individualized ablative irradiation of liver metastases tailored to the daily anatomy with significant superior tumor coverage and improved sparing of OAR.